Techniques in hip arthroscopy and joint preservation surgery - Sekiya, Jon K.; Safran, Marc R.; Ranawat, Anil S. (Saunders/Elsevier, 2011)
Drs. Jon K. Sekiya, Marc Safran, Anil S. Ranawat, and Michael Leunig provide a step-by-step, balanced approach-with contributions from an array of North American and international surgeons-to pre-operative planning, surgical technique, technical pearls, management of complications, and post-operative rehabilitation. Surgical videos on DVD demonstrate techniques such as surgical hip dislocation for femoracetabular impingement and arthroscopic femoral osteoplasty so you can provide your patients with the best possible outcomes. Grasp the visual nuances of each technique through full-color surgical illustrations and intraoperative photographs. Watch expert surgeons perform cutting edge procedures-such as complex therapeutic hip arthroscopy using a femoral distractor, arhroscopic synovectomy and treatment of synovial disorders, surgical hip dislocation for femoracetabular important, and arthroscopic femoral osteoplasty-on DVD. Find information quickly and easily thanks to the consistent chapter format that includes technical pearls.